Plantemateriale frå jordprøver: uviss alder og ubrukt potensial? (AmS-Varia, 2016)
The aim of this paper is to assess the assumptions we make about the age of carbonized and uncarbonized plant materialsfrom soil samples. By questioning the age and origin of plant remains, we investigate an unexploited potential of possiblearchaeological interpretations. As a case study, carbonized and uncarbonized plant remains from a house that dates to thetransition between the Pre-Roman Iron Age and the Roman Iron Age at Hove-Sørbø in Southwestern Norway are investigated. As opposed to the original assumptions based on the preservation conditions at the locality, a total of 1 062 uncarbonized seeds of the arable weeds fat-hen (Chenopodium album) and corn spurrey (Spergula arvensis) are shown to be contemporary with the house. This is a unique find in Norway, and it is assumed that the seeds are a by-product of crop processing, most likely residues from fine sieving of cereal grains. The literature discussing macro analysis and interpretation relevant for Norwegian archaeological contexts is scarce. This is partly due to the fact that analysis of macro remains from such contexts is inherently interdisciplinary, and therefore dependent upon the involvement of archaeologists as well as palaeobotanists for further method development and knowledge production.